Innovation Management and Barriers – Creating Space for Innovation and Organizational Change - Róbert Modranský; Silvia Jakabová; Albert Oláh (Emerging Science Journal, 2020)
The major purpose of this paper is to determine the opportunities and challenges relating to successful innovation management in SMEs in German and Slovakia. The objective and the subjective stances to research comprise three interlinking philosophies: epistemology, ontology and axiology. For this study the major design elements are the explanatory and the exploratory approaches and a case study is the selected research strategy. In order to answer the research problem, numerical and textual data is gathered. The empirical research studies revealed significant cultural influence on innovation management and related organisational change associated with it. It also highlighted substantial differences between success and failure factors in SMEs and large companies and there were implications that formal innovation management was less important from SMEs than for large companies. This research identified key innovation management success factors for SMEs and made three new findings, which add to the current knowledge: innovation circles were an effective innovation management approach to generating and developing ideas and getting innovation to market quickly; government agencies that encourage firms to collaborate effectively enhance the level and success of innovation; SMEs and large companies have distinctly different rankings of barriers to innovation and small and micro firms are more effective in original product innovation and speed to market than medium sized companies.